Negative electrode, preparation method thereof and solid-state battery

By using the design of composite liquid collector negative electrode material and solid electrolyte protective layer in all solid state lithium-ion batteries, the lithium dendrites problem is solved and the cycle stability and safety performance of the battery is improved.

CN119480911APending Publication Date: 2025-02-18ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411636797.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In all-solid-state lithium-ion batteries, existing negative electrode materials are prone to form lithium dendrites during lithium ion deposition, resulting in battery cycle stability and safety issues.

Method used

A composite current collector is used as the negative electrode material, wherein the current collector matrix has a three-dimensional network structure, the negative electrode material includes a lithium-philic carbon-based material and a lithium-philic metal material, and a protective layer of solid electrolyte and lithium-free carbon-based material is constructed on the surface of the composite current collector.

Benefits of technology

Through the design of the negative electrode material and protective layer with a three-dimensional structure, lithium ions can be uniformly deposited, lithium dendrites can be alleviated, and the cycle stability and safety performance of the battery can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480911A_ABST
    Figure CN119480911A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative electrode, a preparation method thereof and a solid-state battery. The negative electrode comprises a composite current collector and a negative electrode protection layer, the composite current collector comprises a current collector substrate and a negative electrode material, the current collector substrate has a three-dimensional network structure, the negative electrode material is distributed in the three-dimensional network structure, and the negative electrode material comprises a lithium-loving carbon-based material and a lithium-loving metal material; the negative electrode protection layer is arranged on at least one side surface of the composite current collector, and the negative electrode protection layer comprises a solid electrolyte and a lithium-phobic carbon-based material. The solid-state battery comprises the negative electrode. The problem of dendritic crystal growth short circuit caused by non-uniform deposition of metal lithium can be relieved, the problem of volume expansion of a full-charge battery can be reduced, and the cycle stability of a solid-state battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a negative electrode and a preparation method thereof, and a solid-state battery. Background Art

[0002] Solid-state batteries inherit the advantages of traditional lithium batteries and have outstanding advantages such as better safety and high energy density. Among solid-state batteries, all-solid-state lithium-ion batteries use inorganic solid electrolytes instead of flammable organic electrolytes to greatly improve the safety of lithium-ion batteries and have received widespread attention from scientific research and industry. However, the density of inorganic solid electrolytes is higher than that of electrolytes, resulting in the energy density of all-solid-state lithium-ion batteries using the same positive and negative electrode systems being lower than that of liquid lithium-ion batteries. Therefore, using a higher capacity negative electrode is the core key to achieving high energy density all-solid-state batteries.

[0003] Among the negative electrodes of solid-state batteries, silicon negative electrodes (theoretical specific capacity of about 4200mAh / g) and metal lithium (theoretical specific capacity of 3860mAh / g) negative electrodes are the preferred negative electrode materials for all-solid-state batteries due to their high specific capacity. However, the volume of the silicon negative electrode expands by up to 300% after lithium is embedded, and there are major interface problems when applied to all-solid-state batteries. Although the side reactions of metal lithium negative electrodes in all-solid-state batteries are lower than those in liquid batteries, it is difficult to resist the problem of lithium dendrites when matched with oxide and sulfide electrolytes, and short circuits are very likely to occur during the battery cycle, affecting the safety and cycle stability of solid-state batteries. Therefore, the development of high-capacity and high-stability negative electrodes is the biggest challenge currently facing the development of all-solid-state batteries.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a negative electrode and a preparation method thereof and a solid-state battery, which can alleviate the problem of lithium dendrites and can help improve the cycle stability of the solid-state battery.

[0006] In order to solve the above technical problems, this application is implemented as follows:

[0007] According to one aspect of the present application, an embodiment of the present application provides a negative electrode, the negative electrode comprising:

[0008] A composite current collector, the composite current collector comprising a current collector matrix and a negative electrode material, the current collector matrix having a three-dimensional network structure, the negative electrode material being distributed in the three-dimensional network structure, and the negative electrode material comprising a lithium-philic carbon-based material and a lithium-philic metal material;

[0009] A negative electrode protection layer is disposed on at least one side surface of the composite current collector, and the negative electrode protection layer comprises a solid electrolyte and a lithium-phobic carbon-based material.

[0010] In addition, the negative electrode according to the present application may also have the following additional technical features:

[0011] In some embodiments, the current collector matrix includes one or more of copper, copper alloy, nickel, nickel alloy, aluminum, aluminum alloy, titanium, titanium alloy or stainless steel.

[0012] In some embodiments, the thickness of the current collector matrix is ​​10 μm to 50 μm.

[0013] In some embodiments, the porosity of the current collector matrix having a three-dimensional network structure is 70% to 96%, and the pore size distribution is 0.1 mm to 2 mm.

[0014] In some embodiments, the nucleation overpotential of lithium deposition of the lithium-philic carbon-based material is ≤20 mV.

[0015] In some embodiments, the lithium-philic carbon-based material includes at least one of carbon black, graphene, carbon nanotubes or carbon fibers, wherein the carbon black includes one or more of acetylene black or Ketjen black.

[0016] In some embodiments, the particle size of the lithium-philic carbon-based material ranges from 0.5 μm to 2 μm.

[0017] In some embodiments, the lithium-philic metal material comprises a nanoscale lithium-philic metal material, and the lithium-philic metal material is selected from metal materials that can react with lithium to form an alloy.

[0018] In some embodiments, the lithium-philic metal material includes at least one of nano-gold, nano-silver, nano-zinc, nano-magnesium, nano-aluminum, nano-platinum, nano-silicon, nano-tin or nano-antimony.

[0019] In some embodiments, the particle size of the lithium-philic metal material ranges from 2 nm to 10 nm.

[0020] In some of the embodiments, the lithium-philic metal material is coated on the surface of the lithium-philic carbon-based material 121 , and / or the lithium-philic metal material is located inside the lithium-philic carbon-based material 1 .

[0021] In some embodiments, the mass of the lithium-philic carbon-based material accounts for 67% to 89% of the total mass of the negative electrode material.

[0022] In some embodiments, the mass of the lithium-philic metal material accounts for 10% to 30% of the total mass of the negative electrode material.

[0023] In some embodiments, the negative electrode material further includes a binder, and the mass of the binder accounts for 1% to 3% of the total mass of the negative electrode material.

[0024] In some embodiments, the binder includes one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinylidene fluoride, polyacrylonitrile or polymethyl methacrylate.

[0025] In some embodiments, the solid electrolyte includes Li (6-x) PS (5-x) M (1+x) Or at least one of yLi2S·(1-y)P2S5, wherein 0≤x≤0.6, 0.2≤y≤0.8, and M is selected from at least one of Cl, Br or I.

[0026] In some embodiments, the particle size of the solid electrolyte is in the range of 0.2 μm to 1 μm.

[0027] In some embodiments, the mass of the solid electrolyte accounts for 5% to 30% of the total mass of the negative electrode protection layer.

[0028] In some embodiments, the nucleation overpotential of lithium deposition of the lithium-phobic carbon-based material is ≥40 mV.

[0029] In some embodiments, the lithium-phobic carbon-based material includes carbon black, and the carbon black includes one or more of acetylene black or Ketjen black.

[0030] In some embodiments, the particle size of the lithium-phobic carbon-based material ranges from 0.05 μm to 0.2 μm.

[0031] In some embodiments, the mass of the lithium-phobic carbon-based material accounts for 68% to 94.5% of the total mass of the negative electrode protection layer.

[0032] In some embodiments, the negative electrode protective layer further comprises a binder, the mass of which accounts for 0.5% to 2% of the total mass of the negative electrode protective layer. Optionally, the binder comprises one or more of nitrile rubber, hydrogenated nitrile rubber, styrene butadiene rubber, isoprene rubber, and butadiene rubber.

[0033] In some embodiments, the thickness of the negative electrode protection layer is in the range of 2 μm to 8 μm.

[0034] In some embodiments, the negative electrode further includes a lithium replenishing layer, and the lithium replenishing layer is located between the composite current collector and the negative electrode protection layer.

[0035] In some embodiments, the lithium supplement layer is made of metal lithium foil.

[0036] In some embodiments, the thickness of the lithium replenishing layer is in the range of 2 μm to 10 μm.

[0037] In some embodiments, the thickness of the negative electrode is in the range of 20 μm to 80 μm.

[0038] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a negative electrode, the method comprising the following steps:

[0039] Dispersing the lithium-philic carbon-based material in a solvent and mixing them evenly to obtain a solution;

[0040] The solution is formed into carbon spherical particles by spray drying;

[0041] The carbon ball particles are subjected to metal element evaporation to form a lithium-philic metal material on the surface and / or inside of the carbon ball particles to obtain a negative electrode material;

[0042] Applying the slurry containing the negative electrode material to a current collector matrix to obtain a composite current collector;

[0043] A slurry containing a solid electrolyte and a lithium-phobic carbon-based material is coated on at least one side surface of the composite current collector to obtain a negative electrode.

[0044] In some embodiments, after the lithium-philic metal material is formed on the surface and / or inside the carbon sphere particles, it is dispersed into a solvent system with a binder to form a slurry containing a negative electrode material.

[0045] In some of the embodiments, the slurry comprising the solid electrolyte and the lithium-phobic carbon-based material further comprises a binder.

[0046] According to another aspect of the present application, an embodiment of the present application provides a solid-state battery, which includes the negative electrode as described above, or includes a negative electrode prepared according to the above method.

[0047] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0048] In an embodiment of the present application, the negative electrode provided includes a composite current collector and a negative electrode protective layer, wherein the current collector matrix in the composite current collector has a three-dimensional network structure, the negative electrode material can be distributed in the three-dimensional network structure, and the negative electrode material includes a lithium-philic carbon-based material and a lithium-philic metal material, so that the negative electrode material is formed by fusing the lithium-philic carbon-based material and the lithium-philic metal material, and the negative electrode material is embedded in the current collector matrix. The lithium-philic metal material can induce metallic lithium to be uniformly deposited inside the negative electrode material and the current collector matrix, and the pore space of the three-dimensional network structure of the current collector matrix can be used to store metallic lithium, thereby alleviating the volume expansion effect of the lithium-free negative electrode; further, a negative electrode protective layer is formed on the surface of the composite current collector, and the negative electrode protective layer includes a solid electrolyte and a lithium-phobic carbon-based material. By constructing a negative electrode protective layer containing a solid electrolyte and a lithium-phobic carbon-based material on the surface of the composite current collector, it is possible to avoid direct contact between the deposited metallic lithium and the electrolyte to produce dendrites and interface problems, which is beneficial to improving the cycle life of the solid-state battery.

[0049] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 Shown is a schematic structural diagram of a negative electrode provided in an embodiment of the present invention.

[0051] Figure 2 Shown is a schematic structural diagram of another negative electrode provided in an embodiment of the present invention.

[0052] Description of reference numerals:

[0053] 10-composite current collector;

[0054] 110-current collector matrix;

[0055] 120-negative electrode material; 121-lithium-philic carbon-based material; 122-lithium-philic metal material;

[0056] 20-lithium replenishing layer;

[0057] 30-Negative electrode protective layer. DETAILED DESCRIPTION

[0058] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0059] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0060] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0061] Compared with traditional liquid electrolyte batteries, all-solid-state batteries have the characteristics of good safety. All-solid-state non-negative electrode lithium metal batteries are one of the all-solid-state batteries. Usually, this type of battery does not directly use metallic lithium, but uses the current collector as the negative electrode, which can further improve safety performance, improve energy density and reduce costs. Generally, a non-negative electrode battery refers to a battery with "no negative electrode active material". By not using negative electrode active materials, the non-negative electrode battery can improve the energy density of the battery. The technical principle of a non-negative electrode battery is to deposit the lithium in the positive electrode on the negative electrode current collector through formation charging or during the first charging process of the battery. All-solid-state non-negative electrode lithium metal batteries are one of the non-negative electrode batteries. In practical applications, the existing all-solid-state non-negative electrode lithium metal batteries will cause the growth of lithium dendrites due to the uneven deposition of lithium ions on the negative electrode of the lithium battery. This is mainly due to the weak interaction between the negative electrode structure of the existing non-negative electrode lithium battery or the negative electrode current collector and lithium, resulting in uneven lithium deposition. Uncontrollable lithium deposition will form dendrites, affecting safety performance. In addition, existing all-solid-state lithium batteries also have the problem of negative electrode volume expansion, which also affects the electrochemical performance of the battery. Furthermore, it is necessary to solve the lithium dendrite problem and volume expansion problem of all-solid-state lithium batteries to reduce the safety risks of the battery and the impact on the battery cycle life.

[0062] In view of this, the inventors of the present application have provided a negative electrode and a solid-state battery comprising the negative electrode through a lot of research. The negative electrode can be a three-dimensional lithium-free negative electrode, and the three-dimensional lithium-free negative electrode can be used in solid-state batteries such as all-solid-state negative electrode-free lithium metal batteries. The technical solution of the embodiment of the present application can alleviate the problem of lithium dendrite growth in existing negative electrode-free lithium metal batteries, and can also alleviate the problem of negative electrode volume expansion, thereby achieving the purpose of improving the safety performance and cycle life of the battery. The description of the specific technical solution is shown below.

[0063] like Figure 1 to Figure 2 As shown, in some embodiments, the present application provides a negative electrode, which includes: a composite current collector 10 and a negative electrode protection layer 30.

[0064] The composite current collector 10 includes a current collector matrix 110 and a negative electrode material 120, that is, the composite current collector 10 is mainly composed of a current collector matrix 110 and a negative electrode material 120, the current collector matrix 110 has a three-dimensional network structure, the three-dimensional network structure is a porous structure, the negative electrode material 120 can be distributed or embedded in the three-dimensional network structure, and the negative electrode material 120 includes a lithium-philic carbon-based material 121 and a lithium-philic metal material 122. The negative electrode protective layer 30 is arranged on at least one side of the composite current collector 10, and the negative electrode protective layer 30 includes a solid electrolyte and a lithium-phobic carbon-based material.

[0065] Herein, the term “lithiophilic carbon-based material 121 ” refers to a carbon material having lithiophilicity, that is, a carbon material having affinity for lithium.

[0066] In this article, the term "lithium-phobic carbon-based material" refers to a carbon material with lithium-phobicity, which may cause a slow transfer rate of lithium ions.

[0067] It should be noted that the above-mentioned lithium-philic carbon-based material 121 and lithium-phobic carbon-based material have meanings well known in the art, and conventional carbon materials can be used to change the lithium-philic properties by adjusting the synthesis method of the carbon material or the later solution treatment to achieve lithium-phobic and lithium-philic functions. For example, by controlling the surface energy and dangling bonds of the material so that the surface of the carbon material has high electronic conductivity and is easier to combine with lithium, the surface of the carbon material contains lithium-philic polar groups, and the lithium-philic carbon-based material 121 is obtained. Similarly, the lithium-phobic carbon-based material can also be obtained by adjusting the synthesis method, or it can also be obtained by later solution treatment so that the surface of the carbon material contains lithium-phobic non-polar groups. The present application does not limit the specific method for obtaining the lithium-philic carbon-based material 121 and the lithium-phobic carbon-based material, and it can also be obtained by the above-mentioned method or other methods known in the art.

[0068] In the present application, the composite current collector 10 includes a current collector matrix 110 and a negative electrode material 120. The current collector matrix 110 can play a supporting role, etc. The negative electrode material 120 includes a lithium-affinity material. Different from the conventional method of setting a negative electrode material layer on the surface of the current collector, the present application combines or embeds the negative electrode material 120 (a negative electrode material with lithium-affinity properties) into the pore structure of the current collector matrix 110 with a three-dimensional network structure, which can alleviate the growth problem of lithium dendrites and the volume expansion effect of the lithium-free negative electrode.

[0069] In the present application, the negative electrode provided is a three-dimensional lithium-free negative electrode, which can be used in solid-state batteries, especially in negative-electrode-free all-solid-state lithium metal batteries.

[0070] When the three-dimensional structured lithium-free anode is applied to all-solid-state lithium metal batteries, the problems of lithium dendrite growth and large volume expansion faced by existing all-solid-state batteries can be alleviated. For example, by inducing the uniform deposition of lithium ions in the three-dimensional structure through the refined design of the anode material and structure, the short-circuit problem of dendrite growth caused by the uneven deposition of metal lithium can be alleviated. By utilizing the gaps in the three-dimensional structure to provide effective space for the deposition of metal lithium, the volume expansion problem of fully charged batteries can be greatly reduced. In detail:

[0071] In detail, firstly, the current collector matrix 110 of the present invention has a three-dimensional network structure, which can form a porous structure. The negative electrode material of the present invention fuses a lithium-philic carbon-based material 121, i.e., a lithium-affinity carbon material, with a lithium-affinity metal material 122 to form a three-dimensional structured negative electrode material 120, and combines or embeds the negative electrode material 120 into the pore structure of the current collector matrix 110 having a three-dimensional network structure. The lithium-philic metal material 122 can induce uniform deposition of metallic lithium inside the negative electrode material 120 and the current collector matrix 110, and can utilize the pore space of the three-dimensional network structure of the current collector matrix 110 to store metallic lithium, thereby alleviating the volume expansion effect of the lithium-free negative electrode. Therefore, the negative electrode material 120 is lithium-philic and can induce the uniform deposition or removal of metallic lithium. The current collector matrix 110 can provide a spatial structure for the generation of dendrites to achieve uniform deposition of lithium. It can also use its pore space to store metallic lithium, thereby alleviating the problem of lithium dendrites and the volume expansion effect of lithium-free negative electrodes, which is beneficial to improving the cycle stability and safety performance of solid-state batteries.

[0072] Secondly, the present invention is also provided with a negative electrode protection layer 30, which includes a solid electrolyte and a lithium-phobic carbon-based material, wherein the solid electrolyte can provide a fast ion transmission path, and the lithium-phobic carbon-based material can protect the composite current collector 10 or the alloy (metal) negative electrode, alleviate volume expansion, and inhibit the formation of lithium dendrites. Thus, by constructing a negative electrode protection layer 30 containing a solid electrolyte and a lithium-phobic carbon-based material on the surface of the composite current collector 10, the deposited metal lithium can be prevented from directly contacting the electrolyte to produce dendrites and interface problems, thereby improving the cycle life of the solid-state battery.

[0073] Based on the above, the three-dimensional structure lithium-free negative electrode provided by the present invention solves the problems of uneven deposition and large volume expansion of the metal lithium negative electrode by constructing a three-dimensional current collector filled with an induced alloy (metal) three-dimensional structure negative electrode material 120. At the same time, the negative electrode protective layer 30 constructed by the lithium-phobic carbon-based material and the solid electrolyte constructed on the surface ensures rapid lithium ion transmission while avoiding the formation of lithium dendrites and interface problems of the deposited metal lithium.

[0074] In some embodiments, the negative electrode further includes a lithium replenishing layer 20, and the lithium replenishing layer 20 is located between the composite current collector 10 and the negative electrode protective layer 30. That is, in some cases, the negative electrode may include a laminated composite current collector 10 and a negative electrode protective layer 30; in other cases, the negative electrode may also include a laminated composite current collector 10, a lithium replenishing layer 20, and a negative electrode protective layer 30.

[0075] In order to improve the energy density and cycle life of the solid-state battery, the negative electrode of the present invention is also provided with a lithium replenishing layer 20, that is, a lithium replenishing layer 20 is provided between the composite current collector 10 and the negative electrode protective layer 30, which can be used to replenish the active lithium lost in the all-solid-state battery, or can continuously provide an appropriate amount of lithium source over a long period of time to improve the cycle life of the solid-state battery.

[0076] Thus, in the negative electrode, the lithium replenishing layer 20 is disposed on at least one side of the composite current collector 10 along the thickness direction, and the negative electrode protection layer 30 is disposed on the surface of the lithium replenishing layer 20 away from the composite current collector 10 .

[0077] The above “lithium replenishing layer 20 is disposed on at least one side surface of the composite current collector 10 along the thickness direction” means that the lithium replenishing layer 20 can be disposed on one surface of the composite current collector 10 along its thickness direction, or on two surfaces of the composite current collector 10 along its thickness direction. The “surface” here can be the entire area of ​​the composite current collector 10, or a partial area of ​​the composite current collector 10. This application has no particular limitation on this, as long as the purpose of this application can be achieved.

[0078] As an example, the composite current collector 10 has two surfaces opposite to each other in the thickness direction thereof, and the lithium replenishing layer 20 is disposed on the two opposite surfaces of the composite current collector 10. Further, a negative electrode protection layer 30 is formed on the surfaces of the lithium replenishing layer 20 on both sides. For example, the composite current collector 10 has a first surface and a second surface in the thickness direction thereof, and the lithium replenishing layer 20 and the negative electrode protection layer 30 are disposed sequentially on the first surface, and the lithium replenishing layer 20 and the negative electrode protection layer 30 are disposed sequentially on the second surface.

[0079] It is understandable that, in other embodiments, the lithium replenishing layer 20 may also be stacked on any one of the two surfaces of the composite current collector 10 .

[0080] The inventors have found through in-depth research that when the negative electrode of the present application satisfies the above-mentioned design conditions and optionally satisfies one or more of the following conditions, the performance of the negative electrode of the solid-state battery can be further improved.

[0081] In some embodiments, in the composite current collector 10, the current collector matrix 110 is a current collector having a three-dimensional structure (three-dimensional network structure), and the current collector matrix 110 can adopt a mesh current collector having a porous structure. As an example, the current collector matrix 110 includes, but is not limited to, one or more of copper, copper alloy, nickel, nickel alloy, aluminum, aluminum alloy, titanium, titanium alloy or stainless steel. The current collector matrix 110 is made of metal materials such as metal copper, nickel, titanium, steel, etc.

[0082] It should be understood that the above-mentioned metal current collectors such as copper, nickel, titanium, and steel all use current collectors with a three-dimensional structure, which can provide a spatial structure, inhibit the growth of lithium dendrites, and help improve the electrochemical performance of the negative electrode. In addition, the above-mentioned metal current collector matrix 110 has a certain mechanical strength and can be self-supporting.

[0083] In some embodiments, the thickness of the current collector matrix 110, that is, the three-dimensional structure of the current collector matrix 110, is 10 μm to 50 μm. As an example, the thickness of the current collector matrix 110 can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or any two of the above values. By controlling the thickness of the current collector matrix 110 within the above range, it is helpful to reduce the thickness as much as possible while meeting a certain mechanical strength, so as to reduce costs and improve the overall energy density of the battery.

[0084] In some embodiments, the current collector matrix 110 having a three-dimensional network structure has a porous structure, the porosity of the current collector matrix 110 is 70% to 96%, and the pore size distribution of the porous structure is 0.1 mm to 2 mm. As an example, the porosity of the current collector matrix 110 is 70%, 75%, 80%, 85%, 90%, 95%, 96% or within the range of any two of the above values; the pore size distribution of the pore structure is 0.1 mm, 0.2 mm, 0.5 mm, 0.8 mm, 1 mm, 1.5 mm, 1.8 mm, 2 mm or within the range of any two of the above values. By controlling the porosity and pore size distribution of the current collector matrix 110 within the above range, the current collector matrix 110 can have more pore structures, and the pore space in the three-dimensional structure can be used to store metallic lithium, alleviate the volume expansion effect of the lithium-free negative electrode, and can be used to distribute the negative electrode material 120, induce the uniform deposition of lithium, and alleviate the problem of lithium dendrites.

[0085] In some embodiments, in the negative electrode material 120 of the composite current collector 10, the surface of the lithium-philic carbon-based material 121 has a lithium-philic property, and the nucleation overpotential of lithium deposition of the lithium-philic carbon-based material 121 is ≤20mV. Preferably, the lithium deposition overpotential of the lithium-philic carbon-based material 121 is less than 20mV, for example, it can be 19mV, 18mV, 17mV, 16mV, 15mV, 12mV, 10mV or less than 10mV, etc.

[0086] In some embodiments, the lithium-philic carbon-based material 121 includes, but is not limited to, at least one of carbon black, graphene, carbon nanotubes, or carbon fibers, wherein the carbon black includes one or more of acetylene black or Ketjen black.

[0087] It should be understood that the above-mentioned carbon-based materials, such as carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, carbon fibers, etc. are conventional carbon materials, and their surfaces have lithium-philic properties, and the lithium deposition overpotential is less than 20mV. The surface of the lithium-philic carbon-based material contains lithium-philic polar groups, which is conducive to the deposition of lithium on the surface. The present application does not limit the specific type of polar groups contained on the surface of the lithium-philic carbon-based material 121, as long as its surface contains lithium-philic polar groups, which is conducive to the deposition of lithium on the surface. Any lithium-philic carbon-based material 121 with lithium-philic polar groups on the surface known in the relevant technology can be used, and will not be repeated here.

[0088] In some embodiments, the particle size of the lithium-philic carbon-based material 121 ranges from 0.5 μm to 2 μm. As an example, the average particle size of the lithium-philic carbon-based material 121 can be 0.5 μm, 0.8 μm, 1 μm, 1.5 μm, 1.8 μm, 2 μm, or a range consisting of any two of the above values. By controlling the particle size of the lithium-philic carbon-based material 121 within the above range, it helps to reduce or avoid safety hazards caused by serious growth of lithium dendrites.

[0089] In the present application, the negative electrode material 120 can improve its affinity for lithium by compounding a lithium-philic carbon-based material 121 and a lithium-philic metal material 122 together, utilizing the synergistic effect of the lithium-philic carbon-based material 121 and the lithium-philic metal material 122, effectively controlling the nucleation sites to stabilize lithium deposition, and better guiding the uniform deposition of lithium ions.

[0090] In some embodiments, the lithium-philic metal material 122 includes nano-sized lithium-philic metal material 122 , and the lithium-philic metal material 122 is selected from metal materials that can react with lithium to form an alloy.

[0091] In order to better achieve synergistic cooperation with the above-mentioned lithium-philic carbon-based material 121, a nanoscale lithium-philic metal material 122 (also referred to as a nano-alloy material) is selected, and the nanoscale lithium-philic metal material 122 is preferably selected from metal elements, especially lithium-philic metal materials that can alloy with lithium to form lithium alloys.

[0092] In some embodiments, the lithium-philic metal material 122 (nano-alloy material) is selected from alloy elements that can react with lithium or are lithium-philic, including, but not limited to, any one or a combination of at least two of nano-gold, nano-silver, nano-zinc, nano-magnesium, nano-aluminum, nano-platinum, nano-silicon, nano-tin or nano-antimony. For the sake of brevity, the combinations within the above range are not listed one by one.

[0093] The above-mentioned lithium-philic metal materials 122 can be alloyed with lithium metal to form lithium alloys, which is beneficial to the deposition of lithium ions. That is, the lithium-philicity of the above-mentioned metal materials can induce the uniform deposition of lithium ions, effectively inhibit lithium dendrites, and alleviate the lithium dendrite problem.

[0094] In addition, in other embodiments, the above-mentioned lithium-philic metal material 122 is not limited to the types listed above. Under the conditions of satisfying the requirements of having good lithium-philicity, being able to alloy with lithium, and being conducive to inducing uniform deposition of lithium, the lithium-philic metal material 122 can also adopt other types, which will not be described in detail one by one here.

[0095] In some embodiments, the particle size of the lithium-philic metal material 122 is in the range of 2 nm to 10 nm. As an example, the average particle size of the lithium-philic metal material 122 can be 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, or a range consisting of any two of the above values. By controlling the particle size of the lithium-philic metal material 122 within the above range, it is helpful to reduce or avoid the safety hazards caused by the serious growth of lithium dendrites.

[0096] In some embodiments, the lithium-philic metal material 122 is coated on the surface of the lithium-philic carbon-based material 121 , and / or the lithium-philic metal material 122 is located inside the lithium-philic carbon-based material 121 .

[0097] In the present application, in the negative electrode material 120, the lithium-philic metal material 122 and the lithium-philic carbon-based material 121 can be combined together by physical vapor deposition or chemical vapor deposition to form a three-dimensional structured negative electrode material 120. For example, the lithium-philic metal material 122 can be coated on the surface of the lithium-philic carbon-based material 121, or the lithium-philic metal material 122 can be simultaneously coated on the surface of the lithium-philic carbon-based material 121 and adsorbed inside the lithium-philic carbon-based material 121. In this way, it is more conducive to the synergistic effect of the two, which can improve the affinity for lithium, effectively control the nucleation sites to stabilize lithium deposition, and better guide the uniform deposition of lithium ions.

[0098] In some embodiments, the mass of the lithium-philic carbon-based material 121 accounts for 67% to 89% of the total mass of the negative electrode material 120, that is, in the negative electrode material 120, the mass of the lithium-philic carbon-based material 121 accounts for 67% to 89%, for example, it can be 67%, 68%, 70%, 72%, 75%, 80%, 82%, 85%, 89% or within the range of any two of the above values.

[0099] In some embodiments, the mass of the lithium-philic metal material 122 accounts for 10% to 30% of the total mass of the negative electrode material 120, that is, in the negative electrode material 120, the mass of the lithium-philic metal-based material accounts for 10% to 30%, for example, it can be 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or within the range of any two of the above values.

[0100] In some embodiments, the negative electrode material 120 also includes a binder, and the mass of the binder accounts for 1% to 3% of the total mass of the negative electrode material 120. That is, in the negative electrode material 120, the mass of the binder accounts for 1% to 3%, for example, it can be 1%, 1.5%, 2%, 2.5%, 3% or a range composed of any two of the above values.

[0101] By adding the binder, the negative electrode material 120 can be bonded to the porous structure of the current collector matrix 110 , thereby improving the bonding strength between the negative electrode material 120 and the current collector matrix 110 .

[0102] In some embodiments, in the negative electrode material 120 , the binder includes, but is not limited to, one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinylidene fluoride, polyacrylonitrile or polymethyl methacrylate.

[0103] In the present application, the solid electrolyte in the negative electrode protection layer 30 can provide a fast ion transmission path, thereby ensuring fast lithium ion transmission.

[0104] In some embodiments, the solid electrolyte in the negative electrode protection layer 30 may be an inorganic solid electrolyte, such as a halide solid electrolyte. As an example, the solid electrolyte includes, but is not limited to, Li (6-x) PS (5-x) M (1+x) Or at least one of yLi2S·(1-y)P2S5, wherein 0≤x≤0.6, 0.2≤y≤0.8, and M is selected from at least one of Cl, Br or I.

[0105] In addition, in other embodiments, the above-mentioned solid electrolyte is not limited to the types listed above. Under the condition of meeting the requirements of having good ability to provide fast ion transmission pathways, the solid electrolyte can also adopt other types, which will not be described in detail one by one here.

[0106] In some embodiments, the particle size of the solid electrolyte ranges from 0.2 μm to 1 μm. As an example, the average particle size of the solid electrolyte can be 0.2 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, or a range consisting of any two of the above values. By controlling the particle size of the solid electrolyte within the above range, it helps to better provide a fast ion transmission path and ensure fast lithium ion transmission.

[0107] In some embodiments, in the negative electrode protective layer 30, the surface of the lithium-phobic carbon-based material has a lithium-phobic property, and the nucleation overpotential of lithium deposition of the lithium-phobic carbon-based material is ≥40mV. Preferably, the lithium deposition overpotential of the lithium-phobic carbon-based material is greater than 40mV, for example, 41mV, 45mV, 48mV, 50mV or greater than 50mV, etc.

[0108] In some embodiments, the lithium-phobic carbon-based material includes, but is not limited to, carbon black, including one or more of acetylene black or Ketjen black.

[0109] It should be understood that the surfaces of the above-mentioned carbon materials such as carbon black, acetylene black, and Ketjen black have lithium-repelling properties, and the lithium deposition overpotential is greater than 40mV. The surface of the lithium-repelling carbon-based material contains non-polar groups that are repellent to lithium, which is not conducive to lithium obtaining electrons and depositing on the surface. The present application does not limit the specific type of non-polar groups contained on the surface of the lithium-repelling carbon-based material, as long as its surface contains non-polar groups that are repellent to lithium, which is not conducive to lithium obtaining electrons and depositing on the surface, any lithium-repelling carbon-based material with non-polar groups that are repellent to lithium on the surface known in the relevant art can be used, which will not be repeated here.

[0110] In some embodiments, the particle size of the lithium-phobic carbon-based material ranges from 0.05 μm to 0.2 μm. As an example, the average particle size of the lithium-philic carbon-based material 121 can be 0.05 μm, 0.06 μm, 0.08 μm, 0.1 μm, 0.12 μm, 0.15 μm, 0.18 μm, 0.2 μm, or a range consisting of any two of the above values.

[0111] In some embodiments, the mass of the solid electrolyte accounts for 5% to 30% of the total mass of the negative electrode protection layer 30. That is, in the negative electrode protection layer 30, the mass of the solid electrolyte accounts for 5% to 30%, for example, 5%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range composed of any two of the above values.

[0112] In some embodiments, the mass of the lithium-phobic carbon-based material accounts for 68% to 94.5% of the total mass of the negative electrode protection layer 30. That is, in the negative electrode protection layer 30, the mass of the lithium-phobic carbon-based material accounts for 68% to 94.5%, for example, it can be 68%, 70%, 75%, 78%, 80%, 85%, 90%, 92%, 94%, 94.5% or a range composed of any two of the above values.

[0113] In some embodiments, the negative electrode protection layer 30 further includes a binder, and the mass of the binder accounts for 0.5% to 2% of the total mass of the negative electrode protection layer 30. That is, in the negative electrode protection layer 30, the mass of the binder accounts for 0.5% to 2%, for example, 0.5%, 1%, 1.5%, 2% or a range consisting of any two of the above values.

[0114] In the above-mentioned negative electrode protective layer 30, by making the mass ratio of the solid electrolyte, the lithium-phobic carbon-based material, and the binder within the above-mentioned appropriate range, it is helpful to ensure the addition amount of the solid electrolyte and the lithium-phobic carbon-based material while meeting the bonding requirements, and to avoid the formation of lithium dendrites and interface problems caused by the deposited metallic lithium while ensuring rapid lithium ion transmission.

[0115] Optionally, in the negative electrode protection layer 30 , the binder includes, but is not limited to, one or more of nitrile rubber, hydrogenated nitrile rubber, styrene butadiene rubber, isoprene rubber, and butadiene rubber.

[0116] In some embodiments, the thickness of the negative electrode protection layer 30 ranges from 2 μm to 8 μm. As an example, the thickness of the negative electrode protection layer 30 can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or a range consisting of any two of the above values.

[0117] By controlling the thickness of the negative electrode protection layer 30 within the above range, it is helpful to reduce the thickness as much as possible while meeting the requirements of effectively avoiding direct contact between the deposited metal lithium and the electrolyte to produce dendrites and interface problems, thereby reducing costs and improving the overall energy density of the battery.

[0118] In some embodiments, the lithium supplement layer 20 is made of metal lithium foil. In the present application, by providing the lithium supplement layer 20 made of metal lithium foil, the energy density and cycle life of the all-solid-state battery can be improved.

[0119] In some embodiments, the thickness of the lithium replenishing layer 20 ranges from 2 μm to 10 μm. As an example, the thickness of the lithium replenishing layer 20 can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a range consisting of any two of the above values.

[0120] By controlling the thickness of the lithium replenishing layer 20 within the above range, it is helpful to reduce the thickness as much as possible while meeting the needs of replenishing the active lithium lost in the all-solid-state battery, thereby reducing costs and improving the overall energy density of the battery.

[0121] In some embodiments, the thickness of the negative electrode ranges from 20 μm to 80 μm. As an example, the total thickness of the negative electrode can be 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, or a range consisting of any two of the above values.

[0122] Accordingly, in some embodiments, a method for preparing a negative electrode is provided, the method comprising the following steps:

[0123] Dispersing the lithium-philic carbon-based material 121 in a solvent and mixing the mixture evenly to obtain a solution;

[0124] The solution is formed into carbon spherical particles by spray drying;

[0125] The carbon ball particles are subjected to metal element evaporation to form a lithium-philic metal material 122 on the surface and / or inside of the carbon ball particles to obtain a negative electrode material 120;

[0126] Applying a slurry containing a negative electrode material 120 to a current collector substrate 110 to obtain a composite current collector 10;

[0127] A slurry including a solid electrolyte and a lithium-phobic carbon-based material is coated on at least one surface of the composite current collector 10 to obtain a negative electrode.

[0128] It should be understood that all the features and advantages described above for the “negative electrode” are also applicable to the “method for preparing the negative electrode” and will not be described in detail here.

[0129] In the present application, a negative electrode material 120 comprising a lithium-philic carbon-based material 121 and a lithium-philic metal material 122 can be prepared first, and then the slurry comprising the negative electrode material 120 is applied to the current collector substrate 110 for drying to obtain a composite current collector 10, and then a slurry comprising a solid electrolyte and a lithium-phobic carbon-based material is applied to the composite current collector 10 to obtain a negative electrode. The preparation method of the negative electrode is simple in process, easy to operate, and has strong feasibility. It is easy to implement in process, and the prepared negative electrode has excellent performance, low cost, and is easy to realize industrial production.

[0130] In some specific embodiments, the method for preparing the negative electrode includes the following steps S10 to S70:

[0131] S10, dispersing the lithium-philic carbon-based material 121 in a solvent, mixing evenly, forming a uniformly dispersed solution system, and obtaining a solution.

[0132] Optionally, the solvent in step S10 may be water or other types of solvents that can be used to disperse the lithium-philic carbon-based material 121 .

[0133] S20, forming carbon sphere particles from the above solution by spray drying.

[0134] In step S20, the above solution can be placed in a spray drying device, and the spray drying device is used to spray the solution to form carbon sphere particles, thereby obtaining the lithium-philic carbon-based material 121 within the target particle size range.

[0135] S30, subjecting the carbon sphere particles to metal element evaporation to form a lithium-philic metal material 122 on the surface and / or inside of the carbon sphere particles.

[0136] In step S30, the main purpose is to combine the lithium-philic carbon-based material 121 and the lithium-philic metal material 122 together, such as by using physical vapor deposition or chemical vapor deposition, to combine the two together, and to allow the lithium-philic metal material 122 to be adsorbed on the surface and inside of the lithium-philic carbon-based material 121.

[0137] As an example, in step S30, the carbon ball particles are subjected to alloy element (metal element) vapor deposition in a fluidized bed device to form nano alloy materials on the surface and inside of the carbon ball particles.

[0138] The specific operation mode of step S30, such as time and other conditions, can be selected and set by technical personnel in this field according to actual conditions. For example, the temperature, time and other operating conditions can be adaptively adjusted according to the types of different metal elements (alloy elements). This application does not limit this.

[0139] S40, dispersing the material prepared in step S30 and the binder into a solvent system to form a slurry to be coated, that is, forming a slurry containing the negative electrode material 120. Optionally, the binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinylidene fluoride, polyacrylonitrile, and polymethyl methacrylate, the content of the binder is 1-3%, and the solvent is selected from water or N-methylpyrrolidone.

[0140] S50 , coating the slurry containing the negative electrode material 120 obtained in step S40 onto both sides of the three-dimensional current collector, namely the current collector matrix 110 , and then drying to form a composite current collector 10 .

[0141] Optionally, the drying temperature is 60° C. to 120° C., and the drying time is 1 h to 12 h.

[0142] S60, uniformly dispersing the lithium-phobic carbon-based material, the solid electrolyte, and the binder into the solvent system to form a uniform slurry, that is, forming a slurry containing the solid electrolyte and the lithium-phobic carbon-based material. Optionally, the binder is selected from one or more of nitrile rubber, hydrogenated nitrile rubber, styrene-butadiene rubber, isoprene rubber, and butadiene rubber, and the content of the binder is 0.5-2%, and the solvent is selected from one or more combinations of toluene, xylene, butyl butyrate, and normal alkanes.

[0143] S70 , coating the slurry containing the solid electrolyte and the lithium-phobic carbon-based material obtained in step S60 on the surface of the composite current collector 10 obtained in step S50 , and drying to obtain a negative electrode.

[0144] Optionally, the drying temperature is 60° C. to 100° C., and the drying time is 1 h to 8 h.

[0145] Optionally, before step S70 , the lithium replenishing layer 20 may be composited with the composite current collector 10 , and then the slurry containing the solid electrolyte and the lithium-phobic carbon-based material obtained in step S60 may be coated on the surface of the lithium replenishing layer 20 .

[0146] In some embodiments, a solid-state battery is provided, which includes a negative electrode or a negative electrode prepared according to the aforementioned method.

[0147] Preferably, the solid-state battery is an all-solid-state lithium battery.

[0148] Since the solid-state battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0149] In some embodiments, the solid-state battery further comprises a positive electrode and a solid electrolyte membrane. The solid electrolyte membrane can conduct ions between the positive electrode and the negative electrode and can also prevent the positive and negative electrodes from short-circuiting.

[0150] It should be pointed out that in the solid-state battery of this embodiment, there is no limitation on the specific materials and structures of the positive electrode and solid electrolyte membrane, and the structures and components of the positive electrode and solid electrolyte membrane that can be used for the battery and are known in the art can be selected.

[0151] In order to better understand the present invention, the specific implementation process of the present invention will be described in detail below in a specific implementation mode. The implementation methods described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. If no specific technology or conditions are specified in the implementation method, the technology or conditions described in the literature in the field or the product specification shall be followed.

[0152] Example 1

[0153] 1. Preparation of the negative electrode, including the following steps:

[0154] S10, dispersing lithium-philic carbon nanotubes and graphene in a mass ratio of 8:2 into an aqueous solution to form a uniformly dispersed solution system to obtain a solution. The solution is spray-dried to form carbon sphere particles of 1 μm.

[0155] S20, vapor-depositing 15% by mass of nano-silver particles on the carbon ball particles in a fluidized bed, wherein the particle size distribution of the nano-silver particles is 5-10 nm, forming nano-alloy materials on the surface and inside of the carbon ball particles, and obtaining a three-dimensional negative electrode material.

[0156] S30, dispersing the three-dimensional negative electrode material obtained in step S20 and 2% by mass of a binder polyacrylic acid into an aqueous solution system to form a slurry to be coated with a solid content of 50%, that is, forming a slurry containing the negative electrode material.

[0157] S40, coating the slurry containing the negative electrode material obtained in step S30 on both sides of a 20 μm thick three-dimensional steel current collector with a porosity of 80%, and then drying to form a composite current collector (composite negative electrode) with a thickness of 40 μm.

[0158] S50, laminating a lithium replenishing layer on the surface of the composite current collector prepared in step S40, wherein the lithium replenishing layer is metal lithium with a thickness of 5 μm.

[0159] S60. Mix lithium-phobic carbon black (acetylene black) and solid electrolyte Li6PS5Cl in a ratio of 9:1, and disperse them with binder nitrile rubber in p-xylene solvent to form a slurry with a solid content of 43%; that is, a slurry containing a solid electrolyte and a lithium-phobic carbon-based material is formed.

[0160] S70, coating the slurry containing the solid electrolyte and the lithium-phobic carbon-based material obtained in step S60 on the surface of the lithium replenishing layer, drying, forming a negative electrode protective layer with a thickness of 3 μm, and obtaining a negative electrode.

[0161] 2. Preparation of batteries, including:

[0162] (1) Preparation of positive electrode: The positive electrode active material NCM811, conductive agent conductive carbon black (SP), conductive agent carbon nanotube (CNT), solid electrolyte Li3YCl6 and binder polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 88.5:1:0.5:8:2, rolled into a film and then composited on a current collector to obtain a positive electrode with a thickness of 100 μm.

[0163] (2) Preparation of solid electrolyte membrane: The solid electrolyte Li3PS4 and the binder polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 99:1 and rolled into a film to obtain a solid electrolyte membrane with a thickness of 20 μm.

[0164] (3) Battery assembly: The positive electrode, negative electrode, and solid electrolyte membrane units are die-cut into the designed size, stacked in the order of negative electrode-solid electrolyte membrane-positive electrode, and hot-pressed at 120°C and 0.5 MPa for 60 s. The bare cells are packaged in a soft package and subjected to isostatic pressing at 500 MPa for 3 min to form an all-solid-state battery.

[0165] Example 2

[0166] The difference between Example 2 and Example 1 is that:

[0167] Step S50 is omitted, that is, there is no lithium replenishing layer in the negative electrode of Example 2.

[0168] The rest are the same as in Example 1.

[0169] Example 3

[0170] The difference between Example 3 and Example 1 is that:

[0171] In step S40, the current collector substrate is a three-dimensional copper current collector with a porosity of 70% and a thickness of 15 μm.

[0172] The rest are the same as in Example 1.

[0173] Example 4

[0174] The difference between Example 4 and Example 1 is that:

[0175] In step S10, the lithium-philic carbon-based material used is conductive carbon black.

[0176] The rest are the same as in Example 1.

[0177] Example 5

[0178] The difference between Example 5 and Example 1 is that:

[0179] In step S20, the lithium-philic metal material used is nano zinc particles.

[0180] The rest are the same as in Example 1.

[0181] Example 6

[0182] The difference between Example 6 and Example 1 is that:

[0183] In step S60, the solid electrolyte used is Li3PS4.

[0184] The rest are the same as in Example 1.

[0185] Example 7

[0186] The difference between Example 7 and Example 1 is that:

[0187] In step S60, the lithium-phobic carbon-based material used is lithium-phobic Ketjen black.

[0188] The rest are the same as in Example 1.

[0189] Example 8

[0190] The difference between Example 8 and Example 1 is that:

[0191] In step S10, the mass fraction of the lithium-philic metal material is 10%.

[0192] The rest are the same as in Example 1.

[0193] Example 9

[0194] The difference between Example 9 and Example 1 is that:

[0195] In step S10, the mass fraction of the lithium-philic metal material is 30%.

[0196] The rest are the same as in Example 1.

[0197] Comparative Example 1

[0198] A 20 μm thick metallic lithium was used as the negative electrode.

[0199] Comparative Example 1 uses a metallic lithium negative electrode known in the prior art.

[0200] Comparative Example 2

[0201] The difference between Comparative Example 2 and Example 1 is that:

[0202] The negative electrode protection layer was omitted, that is, Comparative Example 2 only included the composite current collector and the lithium replenishing layer.

[0203] The rest are the same as in Example 1.

[0204] Comparative Example 3

[0205] The difference between Comparative Example 3 and Example 1 is that:

[0206] The negative electrode protection layer and the lithium replenishing layer were omitted, that is, Comparative Example 3 only included the composite current collector.

[0207] The rest are the same as in Example 1.

[0208] Comparative Example 4

[0209] The difference between Comparative Example 4 and Example 1 is that:

[0210] The lithium-philic metal material 122 is omitted, that is, the negative electrode material of Comparative Example 4 only uses a lithium-philic carbon-based material.

[0211] The rest are the same as in Example 1.

[0212] Comparative Example 5

[0213] The difference between Comparative Example 5 and Example 1 is that:

[0214] The lithium-philic carbon-based material 121 is omitted, that is, the negative electrode material of Comparative Example 5 only uses a lithium-philic metal material.

[0215] The rest are the same as in Example 1.

[0216] Performance Testing

[0217] The solid-state batteries obtained in the above embodiments and comparative examples were subjected to electrochemical performance tests, including:

[0218] (1) First efficiency test: Charge at 0.1C rate for the first time and discharge at 0.1C rate. Divide the 0.1C charge capacity by the 0.1C discharge capacity to get the first efficiency.

[0219] (2) Cyclic performance test: starting from the second charge and discharge cycle at 0.5C until the capacity retention rate reaches 80%, that is, until the capacity retention rate of the cycle reaches 80%, the number of cycles (number of turns) is recorded.

[0220] The test results are shown in Table 1 below.

[0221] Table 1 Performance test results of solid-state batteries in various embodiments and comparative examples

[0222] Example First effect (%) Cycle life (number of times) Example 1 94.8 1275 Example 2 89.6 1042 Example 3 93.2 1047 Example 4 94.2 1198 Example 5 91.5 913 Example 6 95.1 1316 Example 7 92.3 1123 Example 8 93.7 1032 Example 9 91.4 1183 Comparative Example 1 87.2 16 Comparative Example 2 94.2 647 Comparative Example 3 87.8 413 Comparative Example 4 91.3 945 Comparative Example 5 92.7 758

[0223] As can be seen from Table 1, compared with Comparative Examples 1-5, the solid-state batteries prepared using the negative electrodes of Examples 1-10 of the present invention have better cycle performance and first effect. The three-dimensional current collector filled with the three-dimensional structural material provided by the present invention has a composite protective layer constructed of electrolyte and lithium-phobic conductive carbon on its surface, which can avoid direct contact between the deposited metallic lithium and the electrolyte to produce dendrites and interface problems, thereby improving the cycle life of the all-solid-state battery.

[0224] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0225] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0226] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0227] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0228] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative electrode, characterized in that: The negative electrode comprises: A composite current collector, the composite current collector comprising a current collector matrix and a negative electrode material, the current collector matrix having a three-dimensional network structure, the negative electrode material being distributed in the three-dimensional network structure, and the negative electrode material comprising a lithium-philic carbon-based material and a lithium-philic metal material; A negative electrode protection layer is disposed on at least one side surface of the composite current collector, and the negative electrode protection layer comprises a solid electrolyte and a lithium-phobic carbon-based material.

2. The negative electrode according to claim 1, characterized in that The current collector matrix comprises one or more of copper, copper alloy, nickel, nickel alloy, aluminum, aluminum alloy, titanium, titanium alloy or stainless steel; and / or, The thickness of the current collector matrix is ​​10 μm to 50 μm; and / or, The porosity of the current collector matrix with a three-dimensional network structure is 70% to 96%, and the pore size distribution is 0.1 mm to 2 mm.

3. The negative electrode according to claim 1, characterized in that The nucleation overpotential of lithium deposition of the lithium-philic carbon-based material is ≤20 mV; and / or, The lithium-philic carbon-based material comprises at least one of carbon black, graphene, carbon nanotubes or carbon fibers, wherein the carbon black comprises one or more of acetylene black or Ketjen black; and / or, The particle size of the lithium-philic carbon-based material ranges from 0.5 μm to 2 μm.

4. The negative electrode according to claim 1, characterized in that The lithium-philic metal material comprises a nano-scale lithium-philic metal material, and the lithium-philic metal material is selected from metal materials that can react with lithium to form an alloy; and / or, The lithium-philic metal material comprises at least one of nano-gold, nano-silver, nano-zinc, nano-magnesium, nano-aluminum, nano-platinum, nano-silicon, nano-tin or nano-antimony; and / or, The particle size of the lithium-philic metal material ranges from 2 nm to 10 nm.

5. The negative electrode according to claim 1, characterized in that The lithium-philic metal material is coated on the surface of the lithium-philic carbon-based material, and / or the lithium-philic metal material is located inside the lithium-philic carbon-based material; and / or, The mass of the lithium-philic carbon-based material accounts for 67% to 89% of the total mass of the negative electrode material; and / or, The mass of the lithium-philic metal material accounts for 10% to 30% of the total mass of the negative electrode material; and / or, The negative electrode material further includes a binder, and the mass of the binder accounts for 1% to 3% of the total mass of the negative electrode material.

6. The negative electrode according to claim 1, characterized in that The solid electrolyte includes Li (6-x) PS (5-x) M (1+x) or at least one of yLi2S·(1-y)P2S5, wherein 0≤x≤0.6, 0.2≤y≤0.8, and M is selected from at least one of Cl, Br or I; and / or, The particle size of the solid electrolyte is in the range of 0.2 μm to 1 μm; and / or, The mass of the solid electrolyte accounts for 5% to 30% of the total mass of the negative electrode protection layer.

7. The negative electrode according to claim 1, characterized in that The nucleation overpotential of lithium deposition of the lithium-phobic carbon-based material is ≥40 mV; and / or, The lithium-phobic carbon-based material includes carbon black, and the carbon black includes one or more of acetylene black or Ketjen black; and / or, The particle size of the lithium-phobic carbon-based material is in the range of 0.05 μm to 0.2 μm; and / or, The mass of the lithium-phobic carbon-based material accounts for 68% to 94.5% of the total mass of the negative electrode protective layer; and / or, The negative electrode protection layer further comprises a binder, the mass of the binder accounts for 0.5% to 2% of the total mass of the negative electrode protection layer; and / or, The thickness of the negative electrode protection layer ranges from 2 μm to 8 μm.

8. The negative electrode according to any one of claims 1 to 7, characterized in that The negative electrode further comprises a lithium replenishing layer, wherein the lithium replenishing layer is located between the composite current collector and the negative electrode protective layer; and / or, The thickness of the lithium supplement layer is in the range of 2 μm to 10 μm; and / or, The thickness of the negative electrode ranges from 20 μm to 80 μm.

9. The method for preparing a negative electrode according to any one of claims 1 to 8, characterized in that: The following steps are involved: Dispersing the lithium-philic carbon-based material in a solvent and mixing them evenly to obtain a solution; The solution is formed into carbon spherical particles by spray drying; The carbon ball particles are subjected to metal element evaporation to form a lithium-philic metal material on the surface and / or inside of the carbon ball particles to obtain a negative electrode material; Applying the slurry containing the negative electrode material to a current collector matrix to obtain a composite current collector; A slurry containing a solid electrolyte and a lithium-phobic carbon-based material is coated on at least one side surface of the composite current collector to obtain a negative electrode.

10. A solid-state battery, characterized in that: The solid-state battery comprises the negative electrode according to any one of claims 1 to 8, or comprises the negative electrode prepared by the method according to claim 9.

Citation Information

Cited By

  • Negative electrode for lithium secondary battery and lithium secondary battery comprising same

    CN120127107A

  • Negative pole piece for solid-state battery, solid-state battery and manufacturing method of negative pole piece

    CN121215684A

  • Slurry for preparing electrode, silicon negative electrode, and solid-state battery

    CN121769019A

  • Slurry for electrode preparation, silicon negative electrode, and solid-state battery

    CN121769019B

  • Composite negative pole piece and solid-state battery

    CN121964512A